Resistance of Modified Hardened Cement Paste to Frost and De-Icing Salts - Gintautas Skripkiūnas; Džigita Nagrockienė; Giedrius Girskas; Eugenijus Janavičius (The Baltic Journal of Road and Bridge Engineering)
Concrete is widely used in the structures of bridges, flyovers, sidewalks and carriageways that are exposed to freeze-thaw cycles in wet conditions and are treated with de-icing salts. Tests were made to examine the effect of sodium silicate solution on the resistance of hardened cement paste to frost and de-icing salts. 5% sodium chloride, calcium chloride and manganese chloride solutions were used as de-icing salts. The deterioration of hardened cement paste was assessed by the changes in compressive strength, ultrasonic pulse velocity, specimen deformations and amount of scaled matter during cyclic freezing and thawing. Test results have revealed that hardened cement paste modified with sodium silicate solution is less subject to destruction when the surface of cement paste is treated with de-icing salt solutions under cyclic freeze-thaw conditions. The research has proved that sodium silicate solution increases the durability of concrete used in road structures.